The effect of cooperative learning method on learning the grammar rules of fifth year primary school students - TAMZOUR, Halima; DADOUNE, Messaoud (Social Sciences Journal, 2021)
Grammar is considered the pillar of the Arabic language. It is a way of acquiring language skills and the means of verifying the correctness and integrity of speech. It is the rules that govern the composition of speech. However, the teaching of Arabic grammar has always suffered from many difficulties; which has led many researchers to emphasize the need to facilitate grammar and simplify its rules for learners, not only in terms of content, but also in terms of ways of presenting and communicating it to learners. It’s the aims of this study by exploring the impact of the Collaborative Learning method in learning grammatical rules for fifth year elementary school students. After presenting a set of traditional, modern and special methods, we chose the collaborative learning method to teach grammar rules in the fifth grade of elementary school. In this research paper, we will present a model of the course of the lesson of dual (Muthana) according to this method, with a follow-up of the results, to ensure that the choice of the collaborative learning method has a positive and clear impact. We’ll also make sure that choosing the right method for teaching grammar makes a difference and works well.